Opsonic phagocytosis of Plasmodium falciparum merozoites: mechanism in human immunity and a correlate of protection against malaria. - Osier, F; Feng, G; Boyle, M; Langer, C; Zhou, J; Richards, J; McCallum, F; Reiling, L; Jaworowski, A; Anders, R; Marsh, K; Beeson, J (BioMed Central, 2014)
BACKGROUND: An understanding of the mechanisms mediating protective immunity against malaria in humans is currently lacking, but critically important to advance the development of highly efficacious vaccines. Antibodies play a key role in acquired immunity, but the functional basis for their protective effect remains unclear. Furthermore, there is a strong need for immune correlates of protection against malaria to guide vaccine development. METHODS: Using a validated assay to measure opsonic phagocytosis of Plasmodium falciparum merozoites, we investigated the potential role of this functional activity in human immunity against clinical episodes of malaria in two independent cohorts (n = 109 and n = 287) experiencing differing levels of malaria transmission and evaluated its potential as a correlate of protection. RESULTS: Antibodies promoting opsonic phagocytosis of merozoites were cytophilic immunoglobulins (IgG1 and IgG3), induced monocyte activation and production of pro-inflammatory cytokines, and were directed against major merozoite surface proteins (MSPs). Consistent with protective immunity in humans, opsonizing antibodies were acquired with increasing age and malaria exposure, were boosted on re-infection, and levels were related to malaria transmission intensity. Opsonic phagocytosis was strongly associated with a reduced risk of clinical malaria in longitudinal studies in children with current or recent infections. In contrast, antibodies to the merozoite surface in standard immunoassays, or growth-inhibitory antibodies, were not significantly associated with protection. In multivariate analyses including several antibody responses, opsonic phagocytosis remained significantly associated with protection against malaria, highlighting its potential as a correlate of immunity. Furthermore, we demonstrate that human antibodies against MSP2 and MSP3 that are strongly associated with protection in this population are effective in opsonic phagocytosis of merozoites, providing a functional link between these antigen-specific responses and protection for the first time. CONCLUSIONS: Opsonic phagocytosis of merozoites appears to be an important mechanism contributing to protective immunity in humans. The opsonic phagocytosis assay appears to be a strong correlate of protection against malaria, a valuable biomarker of immunity, and provides a much-needed new tool for assessing responses to blood-stage malaria vaccines and measuring immunity in populations.